Musical ecologies : instrumental music ensembles around the world - De Bruin, Leon R.; Southcott, Jane (Abingdon, Oxon ; New York : Routledge, 2022)
"Community music around the world reflects the growing and diverse ways humans collectivize and express themselves in ways that articulate our cultural, social and environmental complexity. Revisiting, redevising and reimagining some of the field's approaches, ideologies and contexts, this co edited volume investigates beyond generalist intercultural and internationalist concepts to reveal the complexity of social ways people come together to make music, and to making music be central to this sociality. The authors explore the role community music plays out around the world and how various instrumentally based music making communities operate as ecologies that allow notions of social, political and cultural agency and identities. Chapters cover various instrumental community music ensembles, observing how they, as social microcosms of change and stasis, provide working methods new and old, extol values and model ethical behaviors that are fluid and dynamic, steadfast and unyielding and that contribute to the ebb and flow of people and their agency that remains under researched. Insights are provided on variously functioning ensembles through the world, showing how myriad instrumental music communities act as drivers, complex environments and apparati for musical and social expression that accommodates the musical aspirations of their members. Taken as a whole, this book explores community music and what music making means to people in the twenty first century"--
Introduction. Redefining the Field / Leon R de Bruin and Jane Southcott -- PART 1. MAINTAINING AND DISRUPTING TRADITIONS: CULTURAL, POLITICAL, ENVIRONMENTAL ECOLOGIES OF COMMUNITY MUSIC PRACTICES. Shifting the Conservatory Narrative: Designing University Curriculum that Celebrates Communities' Musics / Te Oti Rakena and John Coulter ; Optimising the Feedback Loop Between Community and Community Ensemble: A Case Study / Adam Starr ; The Venda tshikona Reed-Pipe Dance as Community Music : Mapping the Ecology of a South African Traditional Music / Susan Harrop-Allin and Dean Salant ; An Inclusion Strategy Approach for Deepening Community Music Engagement in Non-Metropolitan Australia / Graham Sattler and Phil Mullen -- PART 2. THE RHYZOMAL ASSEMBLAGE : INTERACTIONS AND LOCALIZED MICRO-SYSTEMS OF INDIVIDUALS' COMMUNAL EXISTENCE. Agua! The flourishing of Latin Music in Melbourne, Australia / Leon R de Bruin ; Synthesis and Embodiment : The Lowell String Project as Complex Musical Ecosystem / Elissa Johnson-Green ; Mount Gambier's Generations in Jazz : The Impact of Community and Cross-Regional Partnerships / Adam Hardcastle ; Friends in Concert: Growing Music Teacher Identities through Community Music Making / Yan Chen Alvyn Eng, Siew Ling Chua and James Lee ; Training and Retaining Traditions : The Grainger Wind Symphony / Jane Southcott and Leon R de Bruin -- PART 3. WIDER MESO-SYSTEMS OF SOCIAL AND CULTURAL CHANGE, EVOLUTION AND INNOVATION. The Armidale Symphony Orchestra : The Ecology of a Regional Orchestra / Alana Blackburn ; Friends in Music : The Chao Feng Chinese Orchestra, Melbourne, Australia / Jane Southcott and Vicky Liao ; The Golden Age Ensemble : A Community Music Partnership / Chi Ying Lam ; PUBlic Choir : Facilitating an Emergent Musicking Community / Graham Sattler ; Jazz, Improvisation, Community : The Affective Constitution of Social Identity / Chris Stover ; Postlude / Leon R de Bruin and Jane Southcott.
Keywords: Music -- Social aspects; Musical groups -- Social aspects; Community music -- History and criticism; Music -- Instruction and study -- Social aspects; MUSIC / Genres & Styles / General